Polypharmacological Insights into Chinese Medicinal Herbs for Pulmonary Hypertension: A Network-Based Review - Dr. Shakeel Ahmad; Dr. Swati Rai; Dr. Sabahat Hasan; Dr. Deepak Yadav; Dr. Vishal Yadav, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pulmonary hypertension (PH) is a complex and life-threatening condition characterized by elevated pulmonary arterial pressure and vascular remodeling. Traditional Chinese Medicine (TCM), with its multi-target and multi-component therapeutic approach, is emerging as a potential complementary strategy. Network pharmacology offers a modern systems-based framework to elucidate the mechanisms by which TCM herbs exert therapeutic effects on PH Objectives To systematically review and analyze the molecular mechanisms and polypharmacological actions of Chinese medicinal herbs in the treatment of pulmonary hypertension using network pharmacology approaches. Methods A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, CNKI, and Google Scholar up to April 2025. Studies were included if they used network pharmacology to explore the effects of TCM or Chinese herbs on PH. Data were extracted on bioactive compounds, molecular targets, signaling pathways, and network analyses. Pathway enrichment and protein-protein interaction (PPI) networks were evaluated using tools like TCMSP, Cytoscape, STRING, and KEGG. Results Fifty-six studies met the inclusion criteria. TCM herbs such as Salvia miltiorrhiza, Astragalus membranaceus, and Ginkgo biloba were frequently investigated. Core bioactive compounds identified included tanshinone IIA, quercetin, baicalin, and astragaloside IV. Key molecular targets regulated by these compounds were AKT1, NOS3, TGF-β1, and HIF-1α. Enrichment analysis highlighted significant involvement of PI3K-Akt, MAPK, TGF-β, and NF-κB pathways. Compound-target-pathway networks confirmed the polypharmacological nature of TCM, with synergistic interactions across multiple disease-relevant nodes. Experimental validations in animal models supported the computational findings in 32% of the studies. Conclusion Network pharmacology reveals that Chinese medicinal herbs modulate multiple molecular targets and pathways central to PH pathogenesis. TCM offers a promising adjunct or alternative approach to conventional therapy by addressing inflammation, vascular remodeling, and endothelial dysfunction through synergistic mechanisms. Further experimental validation and clinical trials are essential to translate these findings into clinical practice.